Analyzing the Link Between Accounting Sensitive Non-Debt Tax Shields and Investment Opportunity Set - Rehman, Mobeen Ur; Butt, Muhammad Arsalan; Khwaja, Muddasar Ghani; Kashif, Muhammad (Public Finance Quarterly, 2023)
The term depreciation refers to an estimate made in accordance to depreciation policies of the firms that also provides companies with tax shelter benefits (most commonly income taxes) and positive changes in investment opportunities. However, with the passage of time, provisions on depreciation relating to income taxes have been liberalized as an inducement directed by tax policies. This study aims to provide empirical evidence of cross-sectional relationship among accounting policy changes, investment opportunities, accounting policy sensitive non-debt tax shields, financial leverage, size and profitability of the firms listed on Pakistan stock exchange thus providing implications regarding size and leverage hypotheses. We adopt price-based proxies to represent investment opportunities by using large cross-sectional sample of firms. Results of the study suggest that these variables share significant relationship and influence managerial discretion in changing the depreciation and inventory valuation policies in response to variations in such dimensions.